Islam, Iman, dan Ihsan sebagai Pilar Kesempurnaan Agama: Pendekatan Maqāṣid al-Qur’an - Nurhayati Nurhayati (Lembaga Yasin AlSys, 2026)
Although the concepts of Islam, iman, and ihsan have been addressed in several previous studies, research that specifically examines these three as pillars of religious perfection within the perspective of Maqāṣid al-Qur’an remains limited. This study aimed to analyze the relationship between Islam, iman, and ihsan in shaping the perfect human (al-insān al-kāmil) spiritually, morally, and socially using a Maqāṣid al-Qur’an approach. The study employed a qualitative method with a library research design by analyzing Qur’anic verses, the hadiths of the Prophet Muhammad, particularly the Hadith Jibril and the views of both classical and contemporary exegetes and maqāṣid scholars. Data were collected through textual study and analyzed using thematic analysis. The findings show that Islam functions as a framework for outward action, iman as the foundation of inward conviction, and ihsan as the peak of spiritual quality that animates both practice and faith. From the perspective of Maqāṣid al-Qur’an, these three are oriented toward the preservation of religion (ḥifẓ al-dīn), purification of the soul (tazkiyat al-nafs), and the realization of holistic human well-being. These results contribute to the development of Maqāṣid al-Qur’an theory and broaden understanding of the integration of the three religious pillars in contemporary life. The study concludes that the integration of Islam, iman, and ihsan constitutes a comprehensive model of religiosity that is relevant for addressing modern life challenges, with theoretical implications for enriching the literature on Maqāṣid al-Qur’an and practical implications for developing more holistic religious education, while also opening opportunities for further exploration of the application of Maqāṣid al-Qur’an principles in current socio-religious contexts.